In what ways did the integration of applied drama methods, used to teach arts, supported Grade 7 learners in the absence of therapists and social workers?: the case of Mulamula Primary School - Maluleke, Susie N (My University, 2017)
This Practice as Research Report investigates the therapeutic role of Applied Drama methods for school learners dealing with social issues in Mulamula Primary School, Limpopo Province, South Africa. The study investigates how the selected Applied Drama methods established by two founding scholars in the field, and apparently newly introduced to African countries, inform each other and provide a significant model when merged. The study argues that the Applied Drama approach as a theatrical method can enhance theatre to help learners address issues of self-empowerment. As such, the Research Report focuses on Practice-based Research Project workshops and the extended findings derived from these processes. Chapter 1 looks at the research question, background to the study, the aims, rationale, methodology, participant observation, personal journaling and ethical considerations. In chapter 2 the Practice as Research (PAR) project is reported in detail. Chapter 3 looks at the central concepts, definitions and history of Applied Drama. Chapter 4 addresses the theories of Applied Drama and their integration into the literature review. Chapter 5 starts to introduce the analysis of the data collected in the practice when the merged methods findings are addressed and how facilitation plays an important role towards the learner's positive learning and transformation. Chapter 6 concludes the analysis. Chapter 7 comprises of a bibliography which concludes the study. Even though the study raises questions about the efficacy of the positive principles of Applied Drama methodologies, this Research Report affirms that the merging of the two selected methods from both Augusto Boal's "Theatre of the Oppressed" and Paulo Freire's "Pedagogy of the Oppressed" allowed participants to engage in reflection in a more positive way in dealing with social issues arising from Applied Drama processes. The Research Report concludes that even though there is still more work to be done in a South African context in relation to the practices explored, the methods have proved to be successful in terms of safe therapeutic support and education for learners. Overall, the study documents and analyzes how I applied Boal's "Theatre of the Oppressed" techniques together with Freire's "Pedagogy of the Oppressed" in facilitating support and learning towards social change amongst school learners.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts in Applied Drama: Theatre in Education to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2017